Tinjauan Konsep Qard dalam Praktek Arisan di Desa Kaplongan Kecamatan Kedokan Bunder Kabupaten Indramayu - Tenda Budiyanto (Khulasah : Islamic Studies Journal, 2019)
Arisan is a form of muamalah activity which basically consists of 2 functions, namely as a means of saving and accounts receivable. It is said to be a means of saving, which can be seen from the return of money equivalent to what was deposited, while it is said to be a means of debts and receivables, namely because there are parties who owe and receivable. The phenomenon of social gathering is a form of community activity to regulate informal economic life to meet useful needs and avoid harm. It's not just a social gathering for money, there are also various social gatherings that occur in society, for example Hajj social gatherings, family social gatherings, sacrificial social gatherings, and so on. As practiced by mothers in Kaplongan Village, Kedokanbunder District, Indramayu Regency, namely Arisan, the staple food is rice. In this research the author raised the thesis title "Overview of the Qard Concept in the Practice of Arisan". The formulation of the problem in this research is as follows: First, what is the practice of social gathering in Kaplongan Village, Kedokanbunder District, Indramayu Regency? Second, what is the practice of social gathering in Kaplongan Village, Kedokanbunder District, Indramayu Regency in terms of the Qard concept?